Inclusion of Persons with Disabilities in Public Employment Policy in Mozambique - Batone, Domingos Carlos (2021)
The paper discusses the inclusion of people with disabilities in the mozambican labor market through two (2) dimensions of public employment policies, namely, the passive ones that provide income support for unemployed people through unemployment insurance and other social subsidies, as well as active ones, aimed at helping unemployed disabled people to return to work with new skills, through training programs and direct job creation in the public and private sectors. although both approaches have their strengths, they will be applied in practice to verify the level of inclusion of people with disabilities in public employment policies, identify alternatives and challenges for their implementation. Using a mixed methodology, bibliographic consultation will be carried out, along with statistics from the 2017 fourth general census and interviews will be applied to the disabled who are part of the TV Surdo organization, dedicated to defending the rights of people with disabilities. However, the continued practices of discrimination and stigmatization increasingly limit their access to the labor market, thus demanding measures that promote affirmative action for this priority group. The study reached the conclusion that public employment policies in Mozambique are predominantly passive, however, subsidies allocated from 2018 to 2021 did not increase, despite the behavior of inflation showing the increase in the high cost of living. thus, it is recommended that passive measures should continue as long as they are more inclusive and employers will need to be socialized to participate in programs that revitalize active policies for this vulnerable group.